Leadership model in improving employee perfoemance CV. Plainthing Group (A study at CV. Plainthing Group) - Apriansyah, Reggy Wulan; Farihanto, Muhammad Najih; Chang, Jian (COMMICAST, 2022)
An effective leadership model can influence the personality of the leader himself. Every leader must be able to have aspects that can support efforts in improving good relations with members of the organization. The reality is that leaders must be able to deal with their members (employees) who have different characters, dispositions, and ideologies, the same as individual human traits who have different traits, attitudes, ways of thinking and views. Therefore, the figure of a leader must have the ability to influence the opinions and attitudes of others in order to carry out employee duties professionally. Employee performance really determines the results of the achievement of organizational performance, it is necessary to have a good system to be able to improve employee performance to support success in leading the company. The method in this study uses qualitative research with a descriptive approach. This research uses Aji's theory which includes Ingarso sung tulodo, Ing madyo mangunkarso, and Tut wuri handayani and also uses Bernandin and Russel's theory which covers the amount of work, work quality, work knowledge, creativity, cooperation, initiative, and personality. The results of this study indicate that the leadership model is very influential in improving employee performance and can also provide the best results for the company so that this increase becomes an achievement for all.